Denopelopia Roback & Rutter from China with emendation of the generic diagnosis (Diptera: Chironomidae: Tanypodinae) - Cheng, Ming; Wang, Xinhua (Zootaxa, 2005)
The genus Denopelopia is recorded from the Oriental and Palaearctic regions for the first time. Denopelopia diaoluonica sp. n., D. bractea sp. n., and D. viridula sp. n. are described from male imagines. A key to all known males of the genus worldwide is presented, and the generic diagnosis is emended.